Are Risk Management And Internal Control Associated With Public Sector Organizational Performance? - Khakim, Lutfi Abdul; Firmansyah, Amrie (Jurnal Riset Akuntansi Terpadu, 2024)
In carrying out its activities, organizations must pay attention to risks that can hinder achieving goals. In addition, control activities are also implemented to ensure that all components of the organization move together to achieve goals. Therefore, this research is conducted to ascertain the influence of risk management and internal control on organizational performance. The research was conducted at the Inspectorate General of the Ministry of Finance with a quantitative approach using a questionnaire. The number of final questionnaires that can be used in this research is 38. This research concludes that risk management and internal control positively affect organizational performance. This research is expected to be used by the Inspectorate General of the Ministry of Finance to develop policies related to risk management and internal control in particular and for the government in a broader context.